2011
DOI: 10.1017/s0266467411000289
|View full text |Cite
|
Sign up to set email alerts
|

Flower number and distance to neighbours affect the fecundity of Goetzea elegans (Solanaceae)

Abstract: Abstract:Pollinator visits to flowers of self-incompatible tropical trees are critical for plant fecundity. However, few studies have examined how much of the variance in tropical tree fecundity is explained by individual attributes of trees (e.g. number of flowers), and how much is due to contextual variables such as distances to nearest flowering neighbours. Using multiple regressions we examined the relative contributions of these factors to the pollination and fecundity of Goetzea elegans, a mainly self-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 46 publications
2
17
0
Order By: Relevance
“…Positive DDD effects on seed production in trees have been reported frequently 29 , 30 , 64 . Pollinators tend to maximize their reward while minimizing energetic expenditures 65 and hence are attracted more to groups of conspecifics than to isolated trees.…”
Section: Discussionmentioning
confidence: 99%
“…Positive DDD effects on seed production in trees have been reported frequently 29 , 30 , 64 . Pollinators tend to maximize their reward while minimizing energetic expenditures 65 and hence are attracted more to groups of conspecifics than to isolated trees.…”
Section: Discussionmentioning
confidence: 99%
“…These studies also looked at the topic entirely from the plant’s point of view and did not measure the effects of vegetation height on visitation frequency or pollinator foraging behaviour. Apart from vegetation height, local density of the same or other plant species ( Bartkowska & Johnston, 2014 ), distance from neighbours ( Caraballo-Ortiz, Santiago-Valentin & Carlo, 2011 ), as well as spatial variation in the proportion of different morphs ( Toräng, Ehrlén & Ågren, 2006 ) can also modify the effects of plant height on its reproductive success.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that the reproductive success of individual plants may decrease in response to increasing NND or decreasing LNS due to pollen limitation (Allison, [1990]; Roll et al [1997]; Jakobsson et al, [2009]; Caraballo-Ortiz et al, [2011]). Contrary to these studies, individual fruit set of C. agristis in our study increased in response to increasing NND and decreased with increasing LNS at the 0.1 m spatial scale, and these relationships remained even when individual plant size was accounted for.…”
Section: Discussionmentioning
confidence: 99%